If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+9=13+x
We move all terms to the left:
5x+9-(13+x)=0
We add all the numbers together, and all the variables
5x-(x+13)+9=0
We get rid of parentheses
5x-x-13+9=0
We add all the numbers together, and all the variables
4x-4=0
We move all terms containing x to the left, all other terms to the right
4x=4
x=4/4
x=1
| 20–5m=4+3m | | -8-m=1 | | 8*x+4=22*3 | | 5x+40=x+20 | | 6+2x=3x-6 | | 7*y=45 | | 5-3x+60=5 | | 5x+13=6x+10 | | 2(x+4)=4x+7-2x+1 | | 6x+26=5x-1 | | 9x-5=10x-14 | | 4x+26x-7=6(5x+9) | | -10+p/2=-12 | | x×x=63 | | x/8=3=12 | | b+2/3=7/3 | | b+2/3=4/1/3 | | g=68 | | -16=8v+2(v+7) | | X2+5x-31=5 | | 3(5x+4)-8x=7x-12 | | x/7=7.04/4 | | 7x+1+11x-18+5x+13=88 | | 0x+9=8x+4 | | 4(z-9)=17 | | 7z=42;z=8 | | 5x−10=90 | | x+9x=100 | | 5x+54=5x+32 | | y+6=17;y=11 | | 4x-2/6=7 | | 5x+54=10x+64 |